Surgical management of a PICC-associated right atrial thrombus: a case report - Tietuo Jin; Rui Wang; RuiJuan Zhang; Gaofeng Pan; Liang Dong (Frontiers in Cardiovascular Medicine, 2026)
A patient who had undergone surgery for breast cancer received a peripherally inserted central catheter (PICC) for chemotherapy. Three months later, she developed chest tightness and dyspnoea. Transthoracic echocardiography and computed tomography revealed a right atrial mass, with the tip of the PICC positioned within the right atrium. After 1 month of anticoagulation with rivaroxaban, the right atrial lesion showed no appreciable reduction in size, and the patient ultimately underwent surgical treatment. Intraoperatively, the mass was found to be closely adherent to the right atrial wall and not connected to the PICC. Histopathological examination demonstrated a mixed thrombus, predominantly composed of fibrinoid material.